Biodiesel production in Africa from non-edible sources: Sources, production, properties and policies - Khalifa Musa Muhammad; Modupe Munirat Adeyemi; Joseph Jacob; Abubakar Rabiu Koko; Kabiru Dauda; Anas Ali Tamasi; Ibrahim Yahuza (Sustainable Chemistry for the Environment)
Energy is crucial in the 21st century as it immensely contributes to growth and development. Fossil fuel serves as the backbone of the world’s energy demand. This source of energy is non-renewable and it adversely affects the environment. Africa suffers from the challenge of energy crisis and this negatively affects the development of the continent. To remedy this, it is pertinent to focus on energy sources that are environmentally friendly. This study highlights the potential of biodiesel production in Africa with a focus on non-edible sources. The sources, emission characteristics, oil content, percentage yield and properties of these samples are stated. These sources do not compete with food so there is no contention of “food versus fuel”. The study clearly highlights the advantages of biodiesel such as high cetane number and flash point; less toxicity; renewable; and biodegradable amongst others. Techniques for enhancing the cold flow properties of biodiesel are stated. Policies and laws that support biodiesel production were discussed. The key factors that should be incorporated in every biofuel policy or legislation was recommended. Biodiesel utilization is in accordance with Sustainable Development Goal 7 “clean and affordable energy”. The study also presents potentials, benefits, challenges, and solution of biodiesel production and utilization in Africa which gives a picture of its socio-economic implications.